The Image of William III in Amsterdam after His Ascent to the English Throne: The Case of the Sheriffs' Election in 1690. (1st September 2016) - Troost, Wouter
Abstract : In 1690 William III and the city of Amsterdam fought out one of their regularly occurring political battles. This time the fight centred around Amsterdam's refusal to send the nomination of the city sheriffs to England, where William III stayed after his ascent to the English throne. Amsterdam appealed to a privilege of Philip II which stated that the nomination should be sent to the Court of Holland in case the stadholder was not in the country. Superficially the conflict dealt with the sheriffs' nomination, but in reality Amsterdam wanted to show William III its independence. The city feared the increased power of their stadholder who had also become the king of England. Moreover the Amsterdam regents thought that the king had subordinated the interests of the Republic to those of England, when he negotiated various treaties with the English in 1689. The political struggle was accompanied by a pamphlet war in which the pro-Amsterdam pamphlets accused the king of wanting to become a sovereign in the Netherlands. The pro-Williamite forces, who were supported by Romeyn de Hooghe and Eric Walten, denied this and blamed the Amsterdammers for playing into the French king's hands by threatening to stop paying for the war against France if their privilege was not upheld. In the end, Amsterdam lost the battle because the other Holland towns did not support Amsterdam's struggle to maintain its privilege.